2022
DOI: 10.1002/ejoc.202200618
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Palladium Catalysis for Aerobic Oxidative Coupling

Abstract: Aerobic oxidative coupling is a dehydrogenative organic transformation in which molecular oxygen acts as a re-oxidant for the catalyst system. Pd has emerged as one of the most popular transition metal catalysts for such reactions. Combinations of Pd with other transition metal catalysts can also provide effective catalytic cycles together with highly atom-and step-economical organic transformations. A synergic Pd catalyst system can promote such reactions with a high degree of efficiency based on a re-oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 107 publications
(178 reference statements)
0
8
0
Order By: Relevance
“…Because the coupling reactions between CÀ H/CÀ H bonds do not require pre-functionalization on either substrate, the CDC reaction is the ultimate short-process coupling reaction. [16][17][18] However, excess amounts of substrate are often required to achieve high reaction conversion and selectivity. Fagnou et al reported a pioneering CDC reaction between an indole derivative and benzene (Scheme 5).…”
Section: Synthesis Of Organic Semiconducting Materials Using the Cros...mentioning
confidence: 99%
See 2 more Smart Citations
“…Because the coupling reactions between CÀ H/CÀ H bonds do not require pre-functionalization on either substrate, the CDC reaction is the ultimate short-process coupling reaction. [16][17][18] However, excess amounts of substrate are often required to achieve high reaction conversion and selectivity. Fagnou et al reported a pioneering CDC reaction between an indole derivative and benzene (Scheme 5).…”
Section: Synthesis Of Organic Semiconducting Materials Using the Cros...mentioning
confidence: 99%
“…Furthermore, cross-dehydrogenative cou-pling (CDC; i. e., CÀ H/CÀ H coupling) reactions do not require the introduction of halogen moieties or organometallic groups, which further shortens the synthesis process (Scheme 1c). [16][17][18] However, this reaction inevitably proceeds with an undesired homo-coupling as a side reaction because both reaction points are CÀ H bonds. Therefore, to establish the CDC reaction as a method for preparing organic optoelectronic materials, high cross-coupling selectivity is required, in addition to the regioselectivity mentioned above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many efficient synthetic strategies have been proposed by the tireless efforts of synthetic chemists, such as Transfer Hydrogenation, [8a–d] Oxidative coupling, [8e–f] C−H bond activation, [8h–i] Decarboxylative coupling [8j–l] and Domino cascade, [8m–n] many new synthetic methods have been developed based on these strategies, in which catalysts play an indispensable role. The presence of catalysts activates the above strategies in the construction of pyrrolo[1,2‐ α ]quinoxalines, which greatly expands the range of substrates for the construction of pyrrolo[1,2‐ α ]quinoxalines, shortens the synthesis steps, and makes the skeleton construction more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Oxidative couplings involve cleavage of ubiquitous bonds such as C-H and heteroatom-H bonds in substrates. 3 This characteristic feature realizes more atom-and step-economical transformations than the other coupling reactions. 4 Oxidative couplings have been inspired by the Wacker process, which is the coupling of ethylene with water, and the process has been developed with a variety of substrates.…”
Section: Introductionmentioning
confidence: 99%